Efektivitas Nilai Electrical Conductivity Terhadap Pertumbuhan Dan Hasil Tanaman Selada Dan Pakchoy Pada Aeroponik Sistem Vertikultur - Husain (Indoensia), Muhammad Fariz (Universitas Tidar, 2023)
This study aims to know the optimal nutritional effectiveness of the plant's growth and production of lettuce and pakchoy plants on aeroponics of the verticultures system. This research was conducted at the PB Mustika Tani greenhouse of the Klaten in July-August 2022. The research uses a Completely Randomized Design (CRD) non-factorial with two levels of grades EC; EC 1.5 mS/cm (E1) and EC of 2 mS/cm (E2). The experiment consists of 3 replications, with each replication consisting of 42 populations, and six samples were taken. Parameters observed included the height of the plant, the number of leaves, the length of the root, the weight of the leaf, the weight of the root, photosynthesis, and the leaf taste of the plant. The data were analyzed using analysis of variance (ANOVA) with a confidence level of 5%. The results showed no significant difference between EC 1.5 mS/cm and EC 2 mS/cm on all observed parameters.. It is concluded that EC 1.5 mS/cm and EC 2 mS/cm treatment of lettuce and pakchoy on aeroponics of the verticulture system do not show any difference in growth and produce, so EC 1,5 mS/cm treatment is more effective for use.Keywords: Aeroponics, Electrical Conductivity, Pak-choi, Lettuce, Verticulture